Análisis de costos de esquemas de transferencia de embriones bovinos utilizados en Colombia - Bolívar, Paula A.; Maldonado Estrada, Juan Guillermo (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In this work an estimated calculation of the cost of three of the most common protocols for superovulation and embryo trasnsfer in Colombia is presented. Estimate costs were defined according to commercial avalilable products at december 2005, taking into account the following sources of costs: 1) Superovulation of donor cows, 2) sinchronization of receptor cows, and 3) personnel. Hormonal schedules that were analyzed included: schedule 1 (S1), sinchronization with progesterone implants, FSH (continuous dose) GnRH (synchronization of ovulation), and AI; schedule 2 (S2), sinchronization with two dose prostaglandins, FSH (continuous dose), LH source and insemination; and schedule 3 (S3), sinchronization with progesterone implants, FSH (continuous dose), prostaglandin, GnRH (36h) after, and AI. Costs were calculated on the basis of 6.3, 6.6, and 10.3 transferable embryos/flush, for schedule 1, 2 and 3, respectively; flushes/donor/year (n = 4), and global pregnancy rate (50 or 100%). The estimated costs for transferable embryo were US 239.8 ( 479.585.7), US 156 ( 312.879.0), y US 115.1 ( 230.186.5) for S1, S2, and S3, respectively. No statistically significant differences (p > 0.05) between schedules were found for cost components. Average costs/transferable embryo were increased to US 359.7 (719.378.6), US 234.7 ( 469.318.4), y US 172.6 ( 345.279.7), respectively, when 50% of transferred embryo losses were included in the analysis. To our knowledge, this is the first report on estimated costs for embryo transfer in Colombia. In this work several cost components for calculating the cost of ET according to each hormonal schedule are provided.